Agriculture Public Spending and Growth in Indonesia - Armas, Enrique Blanco (2012)
This paper analyzes the trends and evolution of public spending in the agriculture sector in Indonesia, as well as the impact of public spending on agricultural growth. It finds that, in line with empirical work undertaken in other countries, public spending on agriculture and irrigation during the period 1976-2006 had a positive impact on agricultural growth, while public spending on fertilizer subsidies had the opposite effect. The composition of spending patterns in Indonesia over the past decade can partly explain why significant increases in public spending for agriculture have not resulted in a commensurate increase of agricultural production. The paper is structured as follows. Section I presents analytical and empirical findings about the impact of overall public spending on growth, with a particular focus on Indonesia, followed by an analysis of the government's role in agriculture. More precisely, it discusses how public spending can contribute to higher productivity and faster growth in the sector. The section draws lessons from the empirical literature and country examples worldwide, exploring the implications of some of these findings in the Indonesia context. Section II presents the results of an empirical analysis of the impact of agriculture public spending on agriculture gross domestic product per capita growth in Indonesia, using time series analysis with both ordinary least squares and generalized method of moments econometric techniques. Section III analyzes in detail agriculture public spending trends in Indonesia over the period 2000-08, highlighting that a large and increasing share of the spending is being allocated to subsidies (fertilizer, credit, seeds) and to fund transfers to farmers and farmers' groups.